Peran Spiritualitas Islam dan Keterlibatan dalam Membentuk Persepsi Etika Mahasiswa - Apollo Daito; Swarmilah Hariani; Lusia Sri Arini (Owner : Riset dan Jurnal Akuntansi, 2026)
Ethical violations in the accounting profession continue to raise global concerns, and universities play a central role in shaping the integrity of future professionals. This study aims to examine the influence of Islamic Spiritual Intelligence (ISI), Love of Money (LOM), and Engagement (ENG) and Accounting Students’ Ethical Perception (ASEP) in Indonesia. Using the framework of Moral Self-Regulation Theory, this research adopts a quantitative approach with an explanatory survey method. Three hundred twenty-two questionnaires were distributed, and 302 valid responses were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with Smart PLS 4.0. The findings show that ISI significantly reduces students' materialistic tendencies (LOM) and enhances their engagement in academic and social activities. ISI also has a direct and indirect effect on students' ethical perceptions. Engagement positively influences ethical perceptions and partially mediates the effects of ISI and LOM. Additionally, the interaction between LOM and ENG negatively impacts ethical perception, indicating that high engagement may buffer the adverse effects of materialism. The study contributes to the literature by highlighting the critical role of spirituality and affective involvement in moral development, especially within Muslim-majority contexts. The findings recommend that higher education institutions integrate spiritual values and student engagement into ethics curricula to promote holistic character education.